Method for the analysis of health personnel availability in a pandemic crisis scenario through Monte Carlo Simulation - Pando Ezcurra, Tamara (2022)
During pandemic times, difficulties and problems related to the health sector are evident as the number of patients coming to health centers is higher compared to normal situations. This increase in the number of patients is typical of the pandemic, due to the high level of contagion in the population. Health personnel have a higher risk of infection, due to their sharing the work of caring for positive patients, so the infection rate is much higher. Hence, it remains necessary to understand the behavior of infection of health personnel, in order to be prepared to deal with the care of patients. Accordingly, in this research, we present a method to estimate different scenarios of infection and assess the probability of occurrence, so we can estimate the infection rate of health personnel. We present a simulation of 21 possible scenarios with 100 workers and a minimum of 80% needed to guarantee patient care. The results show that it is more likely that a 50% contagion scenario will occur, with an acceptable probability of 20%. En tiempos de pandemia, las dificultades y los problemas relacionados con el sector sanitario son evidentes, ya que el número de pacientes que acuden a los centros de salud es mayor en comparación con las situaciones normales. Este aumento del número de pacientes es típico de la pandemia, debido al alto nivel de contagio de la población. El personal sanitario tiene un mayor riesgo de contagio, debido a que comparte el trabajo de atender a los pacientes positivos, por lo que la tasa de contagio es mucho mayor. Por ello, sigue siendo necesario conocer el comportamiento de contagio del personal sanitario, con el fin de estar preparados para afrontar el cuidado de los pacientes. En consecuencia, en esta investigación, presentamos un método para estimar diferentes escenarios de infección y evaluar la probabilidad de ocurrencia, por lo que podemos estimar la tasa de infección del personal sanitario. Presentamos una simulación de 21 escenarios posibles con 100 trabajadores y un mínimo del 80% necesario para garantizar la atención a los pacientes. Los resultados muestran que es más probable que se produzca un escenario de contagio del 50%, con una probabilidad aceptable del 20%.